Localization of area prostriata and its connections with primary visual cortex in rodent. Issue 3 (10th September 2019) - Lu, Weiye; Chen, Shengqiang; Chen, Xiexian; Hu, Jinmeng; Xuan, Aiguo; Ding, Song‐Lin
Abstract: Area prostriata (Pro) has been found to play important roles in the rapid processing of moving stimuli in the far peripheral visual field. However, the specific neural substrates responsible for these functions remain unknown. In this study, we first examined the location, extent, and topography of the rodent equivalent of the primate Pro based on cytoarchitecture and molecular markers. We then identified its intimate connections with the primary visual cortex (V1) using retrograde and anterograde tracers. Our main finding is that medial V1, which receives peripheral visual information, has strong reciprocal connections with the Pro in both rat and mouse while lateral V1 has significantly fewer such connections. The direct V1 inputs to the Pro provide at least one of the shortest pathways for visual information to reach the Pro, and may be crucial to the fast processing of unexpected stimuli in the peripheral visual field. Abstract : Rodent prostriata (Pro) is a distinct area from adjoining regions. The Pro displays strong expression of some genes such as Adcyap1, Htr1a, Calb1, and C1ql2 and unique connectivity. The Pro has strong and weak connections with medial and lateral primary visual cortex (V1), respectively.